Smoking and alcohol consumption behaviors among undergraduate students in Bangkok Metropolitan and Nakhonratchasima Province - Kusoom, Wichitra; Thongvichean, Sulee (Thai Journal of Nursing, 2020)
A descriptive research aimed to survey smoking and alcohol consumption behaviors among undergraduate students in Bangkok Metropolitan and Nakhonratchasima Province. A sample of 425 undergraduate students in the university in Bangkok Metropolitan and Nachonratchasima Province, was purposively selected. Research instrument was a questionnaire on personal data and smoking and alcohol consumption behaviors. Its reliability coefficient using alpha Cronbach was 0.85. Descriptive statistics and t-test were used in data analysis. The results revealed as follows. 1) Students 37.6 % smoked within the past 6 months and 64.9 % of them consumed alcohol. 2) There were no significant differences in smoking behaviors among students with different gender and age (p > .05). Smoking behaviors as well as alcohol consumption behaviors in students who had history of smoking and alcohol consumption of their parents, sibling, and closed friends was higher than those who had no history ( p < .001). 3) There were no significant difference in alcohol consumption behaviors among students in different age group (p > .05). Alcohol consumption behaviors in male student was significantly higher than female students (p < .001).